2022
DOI: 10.2196/33717
|View full text |Cite
|
Sign up to set email alerts
|

Developing, Implementing, and Evaluating an Artificial Intelligence–Guided Mental Health Resource Navigation Chatbot for Health Care Workers and Their Families During and Following the COVID-19 Pandemic: Protocol for a Cross-sectional Study

Abstract: Background Approximately 1 in 3 Canadians will experience an addiction or mental health challenge at some point in their lifetime. Unfortunately, there are multiple barriers to accessing mental health care, including system fragmentation, episodic care, long wait times, and insufficient support for health system navigation. In addition, stigma may further reduce an individual’s likelihood of seeking support. Digital technologies present new and exciting opportunities to bridge significant gaps in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Additionally, efforts should be made to provide individuals with access to appropriate services and care, regardless of their current evidence. 10 The success of this initiative can serve as a reference for other medical teams to provide efficient and highquality care to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, efforts should be made to provide individuals with access to appropriate services and care, regardless of their current evidence. 10 The success of this initiative can serve as a reference for other medical teams to provide efficient and highquality care to patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9 Additionally, the use of Chatbots on smartphones has been shown to improve users' health. 10 By utilizing innovative and intelligent services to assist KFRT patients undergoing PD with home-related health education, home care issues, and new dialysis information, we can use novel communication channels to provide timely information to patients. Experimental studies have shown that Chatbots effectively enhance learners' academic performance and learning satisfaction, thus demonstrating the significant potential for Chatbot application in nursing education.…”
Section: Introductionmentioning
confidence: 99%
“…For instance CoronaGO and Arogya setu were designed by Indian government to improve care delivery and help to its people during COVID-19 situation [7,25]. AI chatbots with speci c audience were developed for young people (2 cases) [26,27], elder people (1 cases) [28], and health care providers and their families (1 case) [29].…”
Section: Chatbots Characteristicsmentioning
confidence: 99%
“…According to our objectives, all of the reviewed chatbots were arti cial intelligence based. MIRA and Vac Chat, Fact Check chatbots were hybrid type that used Rule-based and arti cial intelligence methods [26,29]. All of AI chatbots were used Natural Language Understanding (NLU) methods to understand user input and provides the appropriate response to the user in a conversational manner.…”
Section: Ai Techniquesmentioning
confidence: 99%
“…Additionally, chatbot studies reported significant improvements in depressive symptoms ( 19 ), anxiety symptoms ( 15 ), ADHD ( 20 ), and psychological distress ( 21 ). Throughout the onset of the COVID-19 pandemic, chatbots have been studied as a tool to offer psychological crisis support ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%